Effects of Anesthesia with Isoflurane, Ketamine, or Propofol on Physiologic Parameters in Neonatal Rhesus Macaques (Macaca mulatta) - Martin, Lauren D (American Association for Laboratory Animal Science, 2014)
Isoflurane, ketamine, and propofol are common anesthetics in human and nonhuman primate medicine. However, scant normative data exist regarding the response of neonatal macaques to these anesthetics. We compared the effects of isoflurane, ketamine, and propofol anesthesia on physiologic parameters in neonatal rhesus macaques. Neonatal rhesus macaques (age, 5 to 7 d) were exposed to isoflurane (n = 5), ketamine (n = 4), propofol (n = 4) or no anesthesia (n = 5) for 5 h. The anesthetics were titrated to achieve a moderate anesthetic plane, and heart rate, blood pressure, respiratory rate, end tidal carbon dioxide, oxygen saturation, and temperature were measured every 15 min. Venous blood samples were collected to determine blood gases and metabolic status at baseline, 0.5, 2.5, and 4.5 h after induction and at 3 h after the end of anesthesia. Compared with ketamine, isoflurane caused more hypotensive events and necessitated the administration of increased volumes of intravenous fluids to support blood pressure throughout anesthesia; no significant differences were observed between the isoflurane and propofol groups for these parameters. In addition, isoflurane resulted in a significantly shorter average time to extubation, compared with both ketamine and propofol. Due to supportive care, other physiologic variables remained stable between anesthetic regimens and throughout the 5-h exposure. These data improve our understanding of the effects of these 3 anesthetics in neonatal rhesus macaques and will aid veterinarians and researchers as they consider the risks and benefits of and resources required during general anesthesia in these animals.